State of the art of ergonomic costs as criterion for evaluating and improving organizational performance in industry (2015)
This study selects, in a structured manner, relevant articles with scientific recognition and simultaneously identifies these publications’ characteristics that may scientifically enrich the proposed topic. The topic involves ergonomic costs as a criterion for evaluating and improving organizational performance in industry. This study uses Proknow-C as a theoretical instrument for intervention. The following results are obtained: a) a bibliographic portfolio of 16 items, aligned with the view adopted by researchers who served as this research’s theoretical framework; b) the Applied Ergonomics journal shows the highest number of scientific articles in the bibliographic portfolio; and c) Ergonomics, Costs, and Evaluation are the most frequent keywords. The studies selected using the methodology indicate that successful ergonomic projects result in substantially reduced production costs and associated economic and financial gain for the industry.